2019
DOI: 10.1080/02678373.2019.1592263
|View full text |Cite
|
Sign up to set email alerts
|

Leading well: Challenges to researching leadership in occupational health psychology – and some ways forward

Abstract: Studies on the effects of leadership in occupational health psychology build on the assumption that leaders influence their followers' health and well-being. Although this assumption has received support, this introductory paper to a special issue of Work & Stress on leadership argues that a number of questions regarding leadership and follower health and well-being remain unanswered. We identify four issues that we argue warrant further attention. First, what is "good" leadership? Particular leadership types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
104
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(106 citation statements)
references
References 59 publications
2
104
0
Order By: Relevance
“…To the best of our knowledge, leadership has not been considered a moderating factor of the effects of perceived overqualification. This is surprising because leadership is one of the most important contextual variables in the workplace that has been found to deeply influence employees' workplace attitudes and behaviors (Nielsen & Taris, 2019). Considering symbolic interactionism perspective of identity, in the present research, we identified leader humility as a moderator that strengthens the positive effects of perceived overqualification on employees' career identity.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, leadership has not been considered a moderating factor of the effects of perceived overqualification. This is surprising because leadership is one of the most important contextual variables in the workplace that has been found to deeply influence employees' workplace attitudes and behaviors (Nielsen & Taris, 2019). Considering symbolic interactionism perspective of identity, in the present research, we identified leader humility as a moderator that strengthens the positive effects of perceived overqualification on employees' career identity.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of leadership in creating healthy workplaces has been highlighted in earlier research (Furunes et al, 2018 ; Furunes, 2020 ), but a concept of health-promoting leadership has not yet been well established in occupational health research and models, which, therefore, warrants further exploration and new research. With critical questions being posed on how we can better understand the influence leadership has on the three Healthy Healthcare pillar—workers well-being (Nielsen and Taris, 2019 ), patient safety and care (Sfantou et al, 2017 ), and organizational systems and strategy (Bonardi et al, 2019 )—developments here will have direct relevance for Healthy Healthcare , particularly where research looks at more than one pillar.…”
Section: Healthy Healthcare: Research Agendamentioning
confidence: 99%
“…For example, recent research of Nielsen and Taris (2019) points to the accumulating evidence for an association between leadership or supervisor behavior and positive mental well-being, but no study to date has examined the effects of leaders in developing time-broadening perspectives or workplans for aging healthcare workers (see also Thun and Bakker, 2018;Nikolova et al, 2019). Support from leaders and colleagues can have a positive effect on workers' well-being (Nielsen and Taris, 2019). The current study suggests that high levels of supervisor support can form a significant buffer for maintaining higher levels of external employability in the case of a low future time perspective at work.…”
Section: Discussionmentioning
confidence: 99%